If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(2x + -3) + 4 = 16 + -1(-18) Reorder the terms: 5(-3 + 2x) + 4 = 16 + -1(-18) (-3 * 5 + 2x * 5) + 4 = 16 + -1(-18) (-15 + 10x) + 4 = 16 + -1(-18) Reorder the terms: -15 + 4 + 10x = 16 + -1(-18) Combine like terms: -15 + 4 = -11 -11 + 10x = 16 + -1(-18) Multiply -1 * -18 -11 + 10x = 16 + 18 Combine like terms: 16 + 18 = 34 -11 + 10x = 34 Solving -11 + 10x = 34 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '11' to each side of the equation. -11 + 11 + 10x = 34 + 11 Combine like terms: -11 + 11 = 0 0 + 10x = 34 + 11 10x = 34 + 11 Combine like terms: 34 + 11 = 45 10x = 45 Divide each side by '10'. x = 4.5 Simplifying x = 4.5
| 2(4-2x)-3(x+5)=5x-2 | | 13=4+s | | 4i-8=40 | | 5f-3h+4f-2g+2f=0 | | 5x+24=6x+4 | | 2x^2-4x+7=k | | y=0,25 | | 2x+209=11x-52 | | 9(2+a)+4(2a+9)=11 | | x^2+2k+9=0 | | +n-8=24 | | 6x-8=10-2x | | -9+2x+3x=11 | | -x-11+3x=3 | | x(x-4)=9 | | 3x-1-x=5 | | 4x(16x+3)=12x+9 | | x(5x-1)=7x-3 | | log(2x-3)+log(9-4x)=0 | | 32-4(3+2)-11*3+21=0 | | 25x^2+110x-278=0 | | -12+3x+2x=3 | | ln(2x-3)+ln(9-4x)=0 | | 45+2a=95 | | 3(5-2)-(1-5)=13 | | 2x+x=0.18 | | 4(x-5)=x+1 | | 4m-16=-39 | | 4m-16=39 | | 4(x+6)+x=5x | | x^2-4x+28=0 | | 9-abs(5x-4)=2 |